Race, ethnicity and COVID-19 vaccine concerns: A latent class analysis of data during early phase of vaccination - Jen-Hao Chen; Cheng-Shi Shiu (Elsevier, 2022)
Racial gaps in vaccine uptake in the United States have been widely reported. Existing studies, however, have not explored how individuals' concerns about COVID-19 vaccines are clustered. In this study, racial and ethnic background is linked to constellations of COVID-19 vaccine concerns during the early phase of vaccines in the United States, using the Household Pulse Survey (N = 60,492). Latent class analysis reveals five distinct classes of vaccine concerns: general skepticism, distrust of science and the government, safety, a desire to wait and see, and vague uncertainty. Compared to Whites, people of color more consistently report vaccine hesitancy due to safety and a desire to wait and see, rather than distrust of science and the government. Whites, however, more consistently report general skepticism and distrust of science and the government. Our findings suggest that distrust of science and government is not central to racial minorities' vaccine hesitancy, but it is so for Whites.